Kissinger, Henry. China. Barcelona, Editorial Debate, 2012 (621 p.) ISBN: 978-84-8306-945-5. - Jiménez Cabrera, Diego (Instituto de Estudios Avanzados - Universidad de Santiago de Chile, 2013)
Kissinger, Henry. China. Barcelona, Editorial Debate, 2012 (621 p.) ISBN: 978-84-8306-945-5.